Impact of aquaculture and agriculture nutrient sources on macroalgae in a bioassay study. (December 2021) - Streicher, Michael D.; Reiss, Henning; Reiss, Katrin
Abstract: Eutrophication is a major threat to aquatic ecosystems, because excessive nutrient enrichment may result in the loss of ecosystem services. Fjord systems are specifically under pressure due to nutrient input from land (agriculture) and sea (aquaculture). In this bioassay study, we have analyzed the effect of different nutrient sources, as well as their combination, on growth, nutrient composition and recruitment of habitat-forming and ephemeral macrophytes. We found that agricultural fertilizer increased growth for all algae (except Fucus ), while the fish farm effluents mainly increased growth of Ulva . The C:N ratio was hardly affected by the fish farm, but decreased significantly in all algae when agriculture fertilizer was added. Most interestingly, however, distance to the fish farm modulated the algal response to the fertilizer. Our results demonstrate the importance of studying effects of multiple stressors in aquatic ecosystems to sustainably manage the consequences of anthropogenic impacts. Highlights: Experimental bioassay study on multiple nutrient effects on macroalgae Aquaculture effluents affected mainly growth of the annual algae Ulva . Agriculture fertilizer increased growth for all algae except Fucus . Algal C:N ratio was affected by agriculture fertilizer but not aquaculture effluents. Distance to the fish farm modulated the algal response to the fertilizer.